Synthesis,characterization and investigation of chelating and antimicrobial activities of 4-((-1h-benzo(D)imidazol-l-yl)methylamino)-2-hydroxylbenzonic acid and its 2- substituted derivatives - Fasasi, Semiudeen Abimbola (Obafemi Awolowo University, 2019)
xiv,110